(3GJNGP GdbQGQ Hjf GdYde hGdGHJcGQ (B/s - (3eGgQ, CMeOs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2007)
(3GdHGH GdGhd ebOeI aj GJNGP GdbQGQ GdeTGcd hGdbQGQGJ , gd fMf eKGdjhf aj GJNGP GdbQGQ , eGgh feWc aj GJNGP GdbQGQ GdHGH GdKGfj JMOjO GdeTcdI GdhYj HhLhO eTcdI , JTNjU GdeTcdI GdHGH GdKGdK (B: (3HOGFd GdMd GdeONd GdYdej aj dHMK Yf HOGFd , GdWQb GdGHJcGQjI GdHGH GdQGHY Jbjje GdHOGFd GdHGH GdNGeS JfajP GdbQGQ heJGHYJgs
(3HjHdjhZQGajG(B: (3U(B. 513s
Keywords: (3GJNGP GdbQGQs; (3GdGHJcGQs